Perbandingan Kinerja Keuangan Perusahaan Pulp dan Kertas di Indonesia - Devi Alita Solehsi; Reginata Saharany Kustanti; Mukhamad Sholikudin; Yunia Six Putri Hermanto; Muhammad Nabil Fatwa; Cholis Hidayati (Jurnal Mutiara Ilmu Akuntansi, 2025)
The paper industry plays a crucial role in supporting the economy, particularly in Indonesia, through the printing, packaging, and export-import sectors. However, technological advancements have introduced new challenges, demanding companies to manage resources efficiently and improve financial performance. This research adopts a descriptive comparative method, analyzing the financial performance of five pulp and paper companies: PT Indah Kiat Pulp & Paper Tbk, PT Alkindo Naratama Tbk , PT Suparma Tbk, PT Fajar Surya Wisesa Tbk, and PT Toba Pulp Lestari Tbk. The study uses financial reports from 2019 to 2023 and evaluates liquidity, solvency, profitability, and activity ratios. Results indicate that INKP demonstrates the best liquidity, SPMA excels in activity efficiency, and SPMA also leads in solvency ratios. INKP records the highest profitability. Major challenges include raw material price fluctuations, market demand shifts, and sustainability requirements. The study concludes that to enhance competitiveness, companies should improve asset management and optimize financial structures. This approach aims to help firms face industry competition and seize future opportunities.